Capacity management of an electricity service centre using simulation. (1st January 2011) - Michael, Sony; Mariappan, V.
In today's competitive power market integrated with industrial growth, capacity management becomes a perennial technical issue. Power utilities lose customers when they lack sufficient capacity to provide their demanded service which severely affects the business process of the industries. Interruption time is one of the key characteristics of quality service and customer satisfaction. Higher the frequency of it may even force customer to switch over, resulting in a situation of loss of customer. While additional capacity improves service quality, but the cost for providing capacity increases. Electrical service centre of Goa Electricity Department is a customer complaint redressing mechanism hence its modelling becomes essential for investigating its efficacy. Thus the whole scenario gets placed in non-exponential and dynamic, wherein the classical stochastic models become transcendental. Using discrete event simulation, the working of electrical customer service centre was modelled and coded in general purposes simulation system.